Cognitive Biases in Digital Gambling: Insights from the South African Context - Michael Mncedisi Willie (International Journal of Counseling and Psychotherapy, 2026)
Background: The rapid growth of digital gambling platforms has transformed consumer engagement while increasing psychological vulnerabilities, particularly cognitive biases that distort decision-making and risk perception. Objective: This study aims to analyse how cognitive biases influence consumer behaviour in digital gambling environments in the South African context, focusing on the interactions among cognition, platform design, and socio-economic factors. Method: A qualitative document analysis was employed, synthesising multidisciplinary literature from cognitive psychology, behavioural economics, and digital marketing to identify patterns of bias activation and reinforcement. Results: The findings reveal that overconfidence, the illusion of control, and the availability heuristic are systematically exploited through gamification, personalised marketing, and algorithmic targeting, leading to increased engagement and risk-taking behaviour. Socio-economic pressures and cultural narratives of financial mobility further intensify these effects. Conclusion: Cognitive biases operate within a socio-technical system where digital environments actively reinforce irrational decision-making, requiring more comprehensive intervention approaches. Contribution: This study offers an integrated framework that combines cognitive, technological, and contextual dimensions, advancing the development of effective consumer protection strategies, ethical platform design, and responsible gambling policies.